COMUNICAÇÃO E MEIO AMBIENTE NO FORTALECIMENTO DA MARCA - Cazzali, Antonio Rogério (2006)
This dissertation aim to enlarge the discussion about environment and communication to strengthen trade marks and consolidation of corporation good image. This study was based on qualitative researches with some of the most active companies in Brazil, representing significant sectors, that demonstrated not only to utilize the nature preservation support but, in a great array, in to accomplishment of social responsibility, gain credibility in the presence of the consumer and the society, on a symbolic exercise to surpass, where there are no guilty. The change of focus occurred in the ´80s decade, when the companies decided to reinforce their trade marks instead of the goods production, revealed, from the corporation view, being a very interesting alternative to raise earns. This strategy has made the companies to linking their trade marks to the good social action environment, what has begotten some improvement and signalized that this posture is already a market differential. Even though all the planed symbolism and the capital power, there is still the cities devastation by the nature anger, on an obligated conscience matter exercise that will dictate better and transparent human relations in a near future.